Pengaruh Viral Marketing, Turbo Marketing Melalui Trust Terhadap Repurchasing Decision Pengguna Tokopedia - Rusni, Rusni; Tahir, Bungatang; Jabir, Muh; Albar, Elyas; Umar Data, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
This paper analyzes the effect of Viral Marketing and Turbo Marketing on Repurchasing Decisions both directly and indirectly through Trust as mediating variable. The research respondents were 376 college students who had ever made online transaction in Tokopedia. Questionnaire was used to acquire the data to be analyzed by SmartPLS 3.0. Results of this research indicate that Viral Marketing does not have effect on Repurchasing Decision. Meanwhile, Turbo Marketing has a significant positive effect on Repurchasing Decision. As a mediating variabel, Trust is a weak mediator in the effect of Viral Marketing on Repurchasing Decision, but it is a strong mediator in the effect of Turbo Marketing on Repurchasing Decision.